DevOps – foundations and perspectives - Sousa, Leandro (2019)
DevOps is often defined by information technology professionals as a movement, cultural or professional, that brings a new approach to the delivery of software applications through the close collaboration between the development and operations teams. It is grounded by a diverse set of principles, such as culture, automation, lean, monitoring and sharing; and practices, such as, continuous integration and continuous deployment. This article aims to review various aspects of DevOps, highlighting the main benefits and barriers of its adoption.